A model of Islamic animated infographic as an innovative approach for digital Da’wah dissemination / Nur Nazihah Rahim … [et al.] - Rahim, Nur Nazihah; Khidzir, Nik Zulkarnaen; Mohd Yusof, Anuar; Saidin, Aznan Zuhid (Academy of Contemporary Islamic Studies (ACIS), 2018)
The animated infographic is becoming increasingly popular because it can attract audience attention instead of simply writing. It becomes a practical approach in disseminating information in most appealing, fun and easiest way. As people are living in myriad information, somehow it creates some problems such as confusing and difficult in recalling such information. Thus, it is unable to give an understanding for each information. Despite this, animated infographics could be a solution to convey the information successfully. Moreover, in this context of the study, Islamic animated infographic turns into one of an innovative approach to convey the Islamic da’wah in the digital era. There were still limited studies to assist in producing a model for Islamic animated infographic for da’wah dissemination. Moreover, there was a lack of reference on Islamic animation specifically in Islamic animated infographic corresponding with the nature of da’wah dissemination through digital towards Muslim community in Malaysia. Therefore, this study intends to develop a model of Islamic animated infographic as an innovative approach in digital da’wah. The method of this study was using assessment by the experts and survey of the 111 respondents both in Islamic background and design field. The significance of the research revealed that the Islamic animated infographic model can gives total comprehension and absorption of da’wah values to understand and practice in life. Islamic animated infographic model as a tool for da’wah dissemination is not just accepted by the audience as mere entertainment but also for the purpose of da’wah dissemination as well. It can be concluded that Islamic animated infographic could be an innovative approach in disseminating da’wah using digital technology towards the Muslim community in Malaysia by express the beauty of Islam through a creative and attractive approach.